Multiple solutions for a modified quasilinear Schrödinger elliptic equation with a nonsquare diffusion term - Zhang, Xinguang; Liu, Lishan; Wu, Yonghong; Wiwatanapataphee, Benchawan (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we establish the results of multiple solutions for a class of modified nonlinear Schrödinger equation involving the p-Laplacian. The main tools used for analysis are the critical points theorems by Ricceri and the dual approach.